Simple Technology to Convert Coconut Shell Waste into Biochar; A Green Leap Towards Achieving Environmental Sustainability - Wibowo, Yudha Gusti; Ramadan, Bimastyaji Surya; Andriansyah, Muhammad (Universitas Diponegoro, 2019)
Pyrolysis is a technology to convert biomass into high-value product such as biochar. Biochar is a bio-based material as well as char that can maintain soil, water and air quality. Biochar can produced by all of plant parts and generated directly from pyrolysis for a few hours in a certain temperature. The quality of biochar production is highly dependent on the pyrolysis temperature, heating rate, particle size, type, and composition of feedstock and reactor conditions. Several study inform that biochar produced by high temperature such as furnace. Application of biochar in soil can solve contaminated soil from pollutants such as toxic metals contamination, low pH issues and degradable soil caused by industrial activities. Therefore, the application of biochar in water ecosystem can solve some problems such as reduce toxic metals content in wastewater. Biochar known can give significant impact to reduce global warming through the reduction of greenhouse gas emissions and the sequestering of atmospheric carbon into soil. This condition is a problem for several areas especially rural area in developing countries. This paper will describe clearly how to produce biochar use simple technology. Thus, this paper will provide useful information for reducing environmental problems especially on rural areas.